2016
DOI: 10.3390/biom6020023
|View full text |Cite
|
Sign up to set email alerts
|

Taurine Bromamine: Reactivity of an Endogenous and Exogenous Anti-Inflammatory and Antimicrobial Amino Acid Derivative

Abstract: Taurine bromamine (Tau-NHBr) is produced by the reaction between hypobromous acid (HOBr) and the amino acid taurine. There are increasing number of applications of Tau-NHBr as an anti-inflammatory and microbicidal drug for topical usage. Here, we performed a comprehensive study of the chemical reactivity of Tau-NHBr with endogenous and non-endogenous compounds. Tau-NHBr reactivity was compared with HOBr, hypochlorous acid (HOCl) and taurine chloramine (Tau-NHCl). The second-order rate constants (k2) for the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…6) 26,42 . Taurine chloramines are produced when the amino acid taurine reacts with HOCl 43 . Such products can be produced from interaction between HOCl and bacteria 26,44 .…”
Section: Discussionmentioning
confidence: 99%
“…6) 26,42 . Taurine chloramines are produced when the amino acid taurine reacts with HOCl 43 . Such products can be produced from interaction between HOCl and bacteria 26,44 .…”
Section: Discussionmentioning
confidence: 99%
“…6,8,13 NCT in combination with NBrT cured a herpes zoster case with remarkably rapid reepithelialization. 14 Natural synthesis of these compounds by myeloperoxidase and eosinophil peroxidase 15 produce redox potential alterations 15 that apart from anti-inflammatory and antimicrobial activity 16 may influence redox control of tissue repair mechanisms. 17 In this case report, the combination of taurine derivatives provided a saving therapeutic solution for a life-threatening chronic wound infected with a multiresistant S aureus in a significantly weakened elderly patient with chronic renal failure.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the consumption of N acTyr was partially inhibited by 10-fold molar excess of methionine, and totally inhibited by cysteine ( Figure 1 b). N acTrp was also submitted to oxidation by Tau-NHCl, which is much less reactive than Tau-NBr 2 [ 32 ]. For this reason, the reactions were conducted for 1 h and the remaining amino acids were measured by HPLC.…”
Section: Resultsmentioning
confidence: 99%
“…This chemical feature of Tau-NBr 2 is related to its intermediate reactivity when compared to other strong and weak oxidizing agents of the same family, such as HOBr, HOCl, and Tau-NHCl. Indeed, a comparison of rate constants among these compounds and several biological targets provide the following general sequence: HOBr > HOCl > Tau-NBr 2 > Tau-NHCl [ 32 ]. Specifically, a comparison between HOCl and Tau-NBr 2 showed that, while the depletion of tryptophan residues in lysozyme was significantly higher using Tau-NBr 2 , the degradation of the protein, evidenced by its aggregation, was only observed using HOCl [ 41 ].…”
Section: Discussionmentioning
confidence: 99%